ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI GAYA KOGNITIF DAN GENDER - Sarah Annisa; Rizki Dwi Siswanto (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2021)
This study aims to analyze and describe students' mathematical communication ability in terms of cognitive style and gender. The method used is descriptive qualitative. The purposive sampling technique was used to select 4 samples comprising of 1 male gender reflective subject, 1 female gender reflective subject, 1 male gender impulsive subject, and 1 female gender impulsive subject. The instrument in this study used the Matching Familiar Figure Test (MFFT) and mathematical communication ability test. We carried data analysis out, namely data categorization and reduction, data presentation, and conclusion drawing. The triangulation technique is done by comparing the results of the subject's mathematical communication ability test with the interview as a test of data validity. The conclusion of this study the mathematical communication ability of the reflective cognitive style subjects, both male and female, were better than the impulsive cognitive style subjects, both male and female. Male gender reflective subjects (S1) are better able to express and interpret mathematical ideas and process information to solve mathematical problems than male impulsive subjects (S3). The female reflective subject (S2) is better able to express mathematical ideas than the male gender impulsive subject (S4).